Performance Of Power Amplifier With Different Matching Techniques For GPS Application - Mohamed Aminuddin, Mai Mariam; Meor Said, Maizatul Alice; Misran, Mohamad Harris; Salleh, Azahari; Ismail, Mohd Muzafar; Sulaiman, Hamzah Asyrani; Abd Rahim, Rosman; Ali, Nur Alisa; Yusop, Norbayah; Ramlee, Ridza Azri; Othman, Mohd Azlishah (AENSI, 2013)

(untitled)
A Power Amplifier (PA) is designed and optimized to have high efficiency,high output power compression,good return loss and high gain for driving it signal to the antenna without any distortion or losses.The objective Has design the 1'4 at GPS L1 frequency 1.575 GHz with at least 10dB gain.Analyze PA is based on type of matching which is stub element,quarter-wave element and lumped element.The entire requirement is determined using calculation and simulated by using AWR software.